Promising genetic sources for the creation of varieties of durum spring wheat in Western Siberia - M. G. Evdokimov; V. S. Yusov; M. N. Kiryakova; L. V. Meshkova; I. V. Pakhotina; D. A. Glushakov (Вавиловский журнал генетики и селекции, 2022)
The study, expansion and preservation of the genetic diversity of the source material, and its purposeful use in hybridization is the basis for the creation of adaptive varieties of durum spring wheat that are resistant to biotic and abiotic factors of the environment of Western Siberia. The objects of research were samples of durum spring wheat. Over the years of research (2000–2020), about 3 thousand samples were worked out from the world gene pool of various countries and regions: from the collection of the VIR, the gene pool from Mexico (CIMMYT) within the framework of the agreement and cooperation program (2000–2007), from 2000 to the present time under the program of the Kazakh-Siberian Spring Wheat Breeding Network (KASIB), from other scientific institutions of Russia in exchange activities. Using generally accepted techniques, the obtained material was studied for a complex of traits: yield, adaptability, grain quality, resistance to diseases. In the cycle of studying the gene pool from CIMMYT, 50 genotypes were identified in terms of yield at the level of the Omskaja jantarnaja standard, 276 grains by test weight, 131 samples by pasta color, 131 samples by resistance to hard smut, and 112 by resistance to powdery mildew. Almost all samples were not affected by leaf rust. The study set showed high sensitivity to extreme conditions and most forms of interest in quality and disease resistance were low-productive in our environment. In KASIB nurseries, 29 samples were identified in terms of yield and adaptability, 29 samples in terms of grain quality, 21 in terms of resistance to diseases, including 8 resistant to stem rust. In the set of varieties received from the VIR, 15 genotypes were adaptive, 16 had high grain quality, 11 were resistant to stem rust. In the breeding material, 17 samples of the local population resistant to stem rust (6 of them were comprehensively resistant) and 25 race-resistant to Ug99 were identified. The genotypes identified as a result of research are of interest as sources of valuable traits.